Exploração da distribuição de gordura intramuscular no músculo longissimus e sua associação com a mesma medida predita por ultrasssonografia - LUANA DE DECO MARÇAL CRUZ (2024)
The research was carried out with the aim of assessing the percentage of intramuscular fat at different points in the longissimus muscle of Nelore cattle. Forty whole male Nelore cattle were used, with an average age of 18 to 24 months. Intramuscular fat was assessed in the longissimus, between the 11th and 13th ribs, using different techniques: in vivo ultrasound (US), and post-mortem visual assessment (VA), ether extract (EE) and visual marbling score (USDA). For each of the evaluations, the muscle area was divided into six quadrants, two proximal (P1 and P2), two intermediate (I1 and I2) and two distal (D1 and D2). The data was evaluated using Pearson's correlation procedure and comparison of means using Tukey's test at a 5% significance level. Principal Components Analysis (PCA) and Partial Least Squares Regression (PLSR) were also carried out using Unscrabler® software. There were significant differences (P<0.05) in all the analyses of ultrasound with ether extract and ether extract with visual evaluation. Principal component analysis of quadrant data from different anatomical sites (11th-12th and 12th-13th) for the EE trait explained 91% of the total variation. The regressions of the EE values obtained in different layers to estimate the total EE value of the sample showed an R2 value of over 0.99 in the calibration. The PCA analyses of all the techniques used to predict the EE values in the different layers (P, I and D), between the 11th and 13th ribs, the US measurements were the most closely related to the EE values, accounting for 66% of the variation in this characteristic. The intramuscular fat percentage values obtained in the layers of the longissimus muscle between the 11th, 12th and 13th ribs as predictors of the total EE percentage in the muscle, obtained coefficients with the greatest weight in the regression equations, obtained by the PLSR method were those obtained from US measurements taken in the middle and distal regions, both between the 11th and 12th and between the 12th and 13th ribs.